GAMBARAN PEMENUHAN GIZI PADA KASUS STUNTING DI DUSUN 4 DESA KINCANG, KECAMATAN RAKIT KABUPATEN BANJARNEGARA - Lia Aria (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2022)
Food intake is related to the nutrients (nutrients) contained in the food eaten. To achieve optimal growth, it is necessary to fulfill nutritional needs, especially in meeting macronutrients. Macronutrients are nutrients that provide calories or energy, needed for growth, metabolism and other body functions. These macronutrients are needed by the body in large amounts, consisting of carbohydrates, proteins, and fats. Unbalanced food intake is related to the lack of fulfillment of nutrients in food so that it becomes one of the factors causing stunting. The purpose of this study was to describe the needs of protein, fat and carbohydrates. The type of research used is quantitative research with a descriptive approach. The population in this study were all toddlers in the village of 81 toddlers. Sampling technique with a total sampling of 12 respondents who experienced stunting. Analysis of the data used is univariate analysis. In this analysis only produces a frequency distribution. The data collection method in this study was carried out through primary data, namely taking data on measurements of weight, height and calculating the nutritional needs of toddlers using the ADIME formula. The results of this study indicate that the need for protein is inadequate by 100%, the need for adequate fat is 58.33% and the need for carbohydrates is inadequate at 58.33%.